Peer mentoring: Enhancing economics first years’ academic performance - Dos Reis, K.M.; Yu, D. (South African Journal of Higher Education, 2018)
South African higher education institutions have been grappling with the high dropout rate, specifically at first year level. Despite universities’ attempts to implement various strategies to increase student retention, there is very little or no empirical warrant to validate these attempts of research in the South African context. Hence, the aim of this study is to explore how discipline-specific peer mentoring impacts first year students’ academic performance. The two most significant findings of this study are that firstly, the mean continuous assessment mark of the mentees (73.6) is significantly higher compared to students who were not mentees and, secondly, the mentees’ final examination performance was also higher (60.9 versus 52.9). This study highlights the possibilities of using peer mentoring to improve first years’ academic performance. The evidence as revealed in the study provides insights into these possibilities. For example, the peer mentees indicated that they the peer mentors weekly motivational messages inspired them to continue with their studies and the continuous support from the peer mentors assisted them to understand the difficult concepts of Economics. While this study did not focus on the peer mentors, we also found that they were willing to participate voluntarily in this programme, as they believed that there are multiple benefits to being a peer mentor. We argue that the implementation of discipline-specific peer mentoring programmes across all disciplines could facilitate student retention and increase the overall pass rate of first year students.